Assessment of lifetime performance of small ruminants under different feeding systems. (29th December 2016) - Amole, T. A.; Zijlstra, M.; Descheemaeker, K.; Ayantunde, A. A.; Duncan, A. J.
Abstract : Evaluation of lifetime productivity of individual animals in response to various interventions allows assessment of long-term investment opportunities for farmers. In order to gain a better understanding of promising feed interventions for improvement of small ruminant production in Southwestern Nigeria, a dynamic modelling approach was used to explore the effect of different feeding strategies on the lifetime productivity of West African Dwarf (WAD) goats. Modifications were made to the current version of Livestock Simulator developed for cattle production to simulate goat production systems particularly for WAD goats. Effects of changes in input parameters (quality of feed and potential adult weight) confirmed the sensitivity of the modelled weight development and reproductive performance. The values of simulated model outputs corresponded well with observed values for most of the variables, except for the pre-weaning mortality rate in the cut-and-carry system where a wide discrepancy between simulated (2.1%) and observed (23%) data was found. The scenario analysis showed that simulated goats in the free grazing system attained sexual maturity and kidded much later than those in the grazing with supplementation and the cut-and-carry systems. The simulated results suggested that goats require supplementation with protein and energy sources, in order to promote lifetime productivity, early sexual maturity and higher birth weight. In terms of economic returns based on feed cost alone, the moderately intense system produced the most profit. We therefore conclude that grazing with adequate supplementation using farm-generated feed resources offers an opportunity for improving smallholder goat production systems in West Africa.